Arabic Language Learning Management in the Qur'ani Cendikia Program (PCQ) Based on George R. Terry's Theory at the Asy-Syadzili 2 Salafiyah Qur'ani Islamic Boarding School - Arya Wahyu Pratama; Nurhidayati; Hanik Mahliatussikhah; Wildana Wargadinata; Ibnu Samsul Huda (Mantiqu Tayr: Journal of Arabic Language, 2024)
This research discusses the management of Arabic language learning through the Qur'ani Cendikia Program (PCQ) based on George R. Terry's theory which was implemented at the Asy-Syadzili 2 Salaf Qur'ani Islamic Boarding School, with a focus on program management and the problems faced. This research used a qualitative descriptive method, carried out at the Salaf Qur'ani Asy-Syadzili 2 Islamic Boarding School in Malang, in 2024. The research subjects were Arabic Language Teachers. The informants were Islamic boarding school administrators, teachers and students. Data collection was carried out using observation, interviews and documents methods. Meanwhile, data analysis uses the Miles and Huberman analysis technique which consists of data collection, data presentation, data reduction, and drawing conclusions. The results of this research reveal that Arabic language learning management is in accordance with George R. Terry's theory which includes planning, organizing, actuating and controlling. The research results show that the implementation of the Cendikia Qurani Program (PCQ) is in accordance with George R Terry's management theory. Apart from that, there are also supporting factors such as support from Islamic boarding schools and the quality of teachers. Research on a program with management theory is still rare, it is hoped that this research can be developed by future researchers.